2022
DOI: 10.3390/separations9120442
|View full text |Cite
|
Sign up to set email alerts
|

Testing Thymol-Based DES for the Elimination of 11 Textile Dyes from Water

Abstract: Textile industries release dangerous wastewater that contain dyes into the environment. Due to their toxic, carcinogenic and mutagenic nature, they must be removed before the discharge. Liquid–liquid extraction has proven to be an efficient method for the removal of these dyes. As extractants, deep eutectic solvents (DESs) have shown excellent results in recent years, as well as presenting several green properties. Therefore, four different hydrophobic DESs based on natural components were prepared thymol:deca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…1 H NMR (300 MHz, CDCl 3 ) δ H (d, J = 6.9 Hz, H-9 and H-10), 2.26 (s, H-7), 3.16 (m, H-8), 4.72 (s, H-11), 6.57 (s, H-5), 6.72 (d, J = 7.8 Hz, H-2), and 7.07 (d, J = 7.8 Hz, H-1). 13 (16), 107 (11), 91 (16), 77 (5), and 65 (4).…”
Section: Isolation Of Thymolmentioning
confidence: 99%
See 1 more Smart Citation
“…1 H NMR (300 MHz, CDCl 3 ) δ H (d, J = 6.9 Hz, H-9 and H-10), 2.26 (s, H-7), 3.16 (m, H-8), 4.72 (s, H-11), 6.57 (s, H-5), 6.72 (d, J = 7.8 Hz, H-2), and 7.07 (d, J = 7.8 Hz, H-1). 13 (16), 107 (11), 91 (16), 77 (5), and 65 (4).…”
Section: Isolation Of Thymolmentioning
confidence: 99%
“…Thymol can also be used for biological applications due to its strong bactericidal activity [1]. Recently, some studies have reported on several applications of thymol (isolated or combined in composites), such as food packaging [3], agricultural products [4], industrial [5] and pharmacokinetic areas [6], and drug delivery with encapsulation [7], and the studies aimed to overcome its hydrophobicity, volatility, and other limitations that could narrow its application. Its antimicrobial activity is directly related to the functional groups present in the molecule, especially the hydroxyl group at the aromatic ring [8].…”
Section: Introductionmentioning
confidence: 99%
“…Villar et al utilized thymol and coumarin-based HDESs for the removal of harmful textile dyes from water. 69 Ozak et al employed thymol and coumarin-based HDESs for Sudan dye extraction from samples of spices. 70 The thymol : coumarin (1 : 1) HDES exhibited better performance as compared to conventional solvents, with advantages like a fast processing and an environmentally friendly method.…”
Section: Introductionmentioning
confidence: 99%
“…71 A fair amount of experimental work exists showing the employment of thymol and coumarinbased HDESs in multiple applications. [68][69][70][71] However, theoretical studies focusing on the formulation mechanism by highlighting various key interactions and the dynamic behavior of thymol and coumarin-based HDESs are not available in the literature.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation